From Scene to Emergency Department: Is Delta Shock Index a Reliable Predictor in Trauma Care? A Meta-Analysis - Cherryl Aurelia; Clara Alverina; Rezy Ramawan Melbiarta; Pesta Parulian Maurid Edwar (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background: Trauma is a leading global cause of morbidity and mortality, with hemorrhage being a highly preventable cause of death. Delta SI (dSI), reflecting time-dependent hemodynamic changes, shows promise, though conflicting data necessitate comprehensive evaluation of its predictive superiority. This study, therefore, aims to assess the diagnostic accuracy of dSI in predicting clinical outcomes among trauma patients.Methods: This systematic review and meta-analysis included eight studies (Jan 2015–Jul 2025) on adult trauma patients evaluating dSI (Emergency Department SI – prehospital SI) for mortality, blood transfusion needs, or Intensive Care Unit (ICU) admission. Searches were conducted across ScienceDirect, PubMed, Scopus, and Taylor & Francis. The risk of bias was assessed using the QUADAS-2.Results: Eight studies (931,954 patients) were included. DSI consistently showed low sensitivity but high specificity. For blood transfusion, sensitivity was 0.411 (0.313–0.517) and specificity was 0.873 (0.802–0.921). For mortality, sensitivity was 0.350 (0.259–0.454) and specificity was 0.821 (0.763–0.867). ICU admission had a sensitivity of 0.21 (0.144–0.298) and a specificity of 0.887 (0.843–0.919). Subgroup analysis of massive transfusion and in-hospital mortality analyses also showed similar trends.Conclusion: Our findings highlight that while DSI demonstrates consistently high specificity across key clinical outcomes—including mortality, transfusion needs, and ICU admission—it suffers from limited sensitivity. However, its optimal utility lies in its integration with comprehensive clinical assessment rather than standalone use.